PENGEMBANGAN MEDIA PEMBELAJARAN BRANCHING SCENARIO BERBASIS POWERPOINT INTERAKTIF PADA MATERI TRI PARARTHA DI SEKOLAH DASAR - I Wayan Satya Narayana; Kadek Aria Prima Dewi PF; Putu Ayu Septiari Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to Develop an interactive learning media based on the Branching Scenario model using Microsoft PowerPoint to enhance students' learning outcomes on the topic of Tri Parartha in fourth-grade Hindu Religious Education at SDN 4 Tulikup. The research employed the 4D development model (Define, Design, Develop, Disseminate), implemented systematically from needs analysis to dissemination. The media was validated by both media and content experts, receiving an “excellent” rating in terms of feasibility. The trial involved a peer tutoring strategy, where fifth-grade students guided fourth-grade students in exploring the media. The results showed a significant improvement in learning outcomes, with a gain score of 0.75 classified as high. Students also responded positively, finding the media engaging, easy to use, and effective in delivering the moral values of Asih, Punia, and Bhakti in a reflective and contextual manner. The media was disseminated via Google Drive (.ppsx format) and supported with a YouTube tutorial for wider access. The findings indicate that this media is not only effective in improving learning outcomes but also supports a more humanistic and meaningful character-based education process. Keywords: Branching Scenario, Interactive PowerPoint, Tri Parartha, Hindu Religious Education, Interactive Learning Media Keywords: Branching Scenario, Interactive PowerPoint, Tri Parartha, Hindu Religious Education, Interactive Learning Media